DESCRIPTION OF POETIC METERS AND VERSES IN TREATISES ON ARUZ SCIENCE - Dilnavoz R. Yusupova (Web of Journals Publishing, 2024)
In the article, the issue of bahr and vezin, which was written in Shaykh Ahmad Tarozi's “Funun al-balagah”, Alisher Navo’i's “Mezon ul-avzon” and Zahiriddin Muhammad Bobur's “Aruz Treatise”, which are Turkish treatises of aruz, was analyzed; It was pointed out that in the first Turkish treatise, “Funun al-balagah”, the classification and recommendation of the bahrs were carried out in a different way. In the treatise, information is shared such as the fact that 40 bahr were examined theoretically, that 20 of these bahrs were not found in the treatises created until Shaykh Ahmad Tarozi, and that they were invented by the author himself. Alisher Navo’i examines 19 bahrs and about 160 verses related to these bahrs in “Mezon ul-avzon”; In Bobur's Treatise on Aruz, two more bahrs, Ariz and Amik, are added to Navo’i's records and recommended, resulting in 21 bahr and 537 wazins in the “Aruz Treatise”. The author of the article came to the conclusion that the science of Turkish aruz reached its peak during the Timurid period.